How effectively do green bonds help the environment? - ElBannan, Mona A.; Löffler, Gunter (Journal of Banking & Finance, 2024)
We document a significantly negative relationship between the volume of issued green bonds and the future carbon intensity of non-financial corporates; this relationship is limited to firms with higher financial constraints and higher credit risk. The findings suggest that green bonds can help firms finance carbon reductions, but they also indicate that a considerable fraction of green bond financing does not lead to measurable benefits for the environment.